Italian consensus on the therapeutic management of uncomplicated acute hematogenous osteomyelitis in children - Andrzej Krzysztofiak; Elena Chiappini; Elisabetta Venturini; Livia Gargiullo; Marco Roversi; Carlotta Montagnani; Elena Bozzola; Sara Chiurchiu; Davide Vecchio; Elio Castagnola; Paolo Tomà; Gian Maria Rossolini; et al. (BMC, 2021)
Abstract Background Acute hematogenous osteomyelitis (AHOM) is an insidious infection of the bone that more frequently affects young males. The etiology, mainly bacterial, is often related to the patient's age, but it is frequently missed, owing to the low sensitivity of microbiological cultures. Thus, the evaluation of inflammatory biomarkers and imaging usually guide the diagnosis and follow-up of the infection. The antibiotic treatment of uncomplicated AHOM, on the other hand, heavily relies upon the clinician experience, given the current lack of national guidelines for the management of this infection. Methods A systematic review of the studies on the empirical treatment of uncomplicated AHOM in children published in English or Italian between January 1, 2009, and March 31, 2020, indexed on Pubmed or Embase search engines, was carried out. All guidelines and studies reporting on non-bacterial or complicated or post-traumatic osteomyelitis affecting newborns or children older than 18 years or with comorbidities were excluded from the review. All other works were included in this study. Results Out of 4576 articles, 53 were included in the study. Data on different topics was gathered and outlined: bone penetration of antibiotics; choice of intravenous antibiotic therapy according to the isolated or suspected pathogen; choice of oral antibiotic therapy; length of treatment and switch to oral therapy; surgical treatment. Conclusions The therapeutic management of osteomyelitis is still object of controversy. This study reports the first Italian consensus on the management of uncomplicated AHOM in children of pediatric osteomyelitis, based on expert opinions and a vast literature review.